Georgia Architectural and Historic Properties Survey of Rural [132] Mid west section of the county, Quitman, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [132] Mid west section of the county, Quitman, Ga. December 1980. Dixie 7th Day Adventist. A one story rectangular plan with gable tin roof, exposed rafters and stucco siding. Sash windows with 6/6 lights. Square bell tower at left makes small portico at bottom with arched entrance. Double front doors. Fair condition. Date of Construction: Unknown. A typical rural church common to these rural areas
Georgia Architectural and Historic Properties Survey of Rural [132] Mid west section of the county, Quitman, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 955 KB (978,061 bytes).
Keywords: Historic buildings; Lowndes County Historical Society (Lowndes County, Ga.); Real property surveys; Brooks County (Ga.); Quitman (Ga.)